Estratégias de leitura e a (re)significação de uma prática de leitura - Alves, Érica Vaz Domingues (2008)
This search pursuit to enquire and to do connections between considerable studies about reading and readers formation, alike we better to comprehend the significant aspects that involve the apprenticeship and development of the reading s practice, as well the teacher s to play part of as motivate agent in this process. With the proposal of the we comprehend the circunstances into the entails between readers and books are constructed, with visions to readers formation, we objectify to treat the reading in the State Public Hammock and to verify the necessity of the use the cognitive strategies in the text signification construction. By to deal about proceedings the comprehend cognitive and metacognitive aspects, the perception of this aspects is fundamental to the development of the reader competence. To the execution of the our search, we elaborated a inquiry questionary destined to teachers and reading proposal directioned to students, that permit to analyse the use and appose of the cognitive strategies in the reading act. Founded by cognitivists theories, we verified that the motivation to the reading, sighting the signification construction, must to be settled in reading strategies, facilitate elements the function like motivate agents and permit to reader to monitor the proper comprehension. Aside of the adopted proceedings to prove our search, we verified that, a general mode, students and teachers use cognitive strategies, in spite of been unprovided of the teoric embasements that enable the systemizetion of this yours reading classes